The marketization of English higher education and the financing of tuition fees. (18th April 2016) - Palfreyman, David; Tapper, Ted
Abstract : This article explores the marketization of English higher education with particular reference to the introduction of undergraduate student tuition fees. It argues that the breakdown of the political consensus that underwrote the public funding of undergraduate student funding was the consequence of ideological and economic changes that, following the threat of some universities to impose top-up fees, resulted in the appointment of the Dearing Committee and thereafter the steady introduction of variable fees up to a ceiling of €9, 000 per annum, repayable through income-contingent loans. It reviews the contemporary breaking of the political consensus on this issue, as evidenced by the Labour Party's promise in the 2015 general election campaign to lower the maximum annual fee to €6, 000, with the further possibility of replacing income-contingent loans with a graduate tax. It concludes by putting forward the policy options that are likely to emerge in the context of the publication of the current government's Green Paper on higher education.